Estudio de prefactibilidad para la instalación de una planta productora de un colorante alimentario azul a base de huito (Genipa americana) - Charri Alvarez, Karla Lizzeth (2021)
The objective of this pre-feasibility study is to demonstrate the technical, economic, and social feasibility of installing a plant to produce a natural food blue colorant based on the fruit of the huito (Genipa americana). This research was motivated by the great growth of a market aware of the sustainability and safety of the products they consume, which is why a trend is observed for natural food colors. Previously knowing that blue remains as one of the most complicated challenges in the industry due to the scarcity of blue pigments in nature, we chose to investigate about huito, a product from our Amazon that despises an eatable intense blue dye. It is expected to develop the product to export to Germany and demonstrate the industrial potential of the fruits that our Amazon offer us. The investment in the project, whose useful life was determined for the years 2022 to 2026, is extremely beneficial, obtaining a net present value (NPV) of 490 237 73 soles at an TEA of 12,83% and a payback period of the investment of approximately 3 years. Likewise, the social impact of the project was corroborated, obtaining that for each sol of investment 6,35 soles of added value is generated and that 0,16 soles of investment are needed to generate 1 sol of added value.